Validity and feasibility of the global leadership initiative on malnutrition diagnostic concept in older people: a literature review from August 2021 to August 2022. Issue 1 (January 2023) - Cederholm, Tommy; Barazzoni, Rocco
Abstract : Purpose of review: Early 2019, the Global Leadership Initiative on Malnutrition (GLIM) concept offered a clinically applicable and objective procedure for diagnosing malnutrition. This review summarizes 40 publications from August 2021 to August 2022 that applied the GLIM criteria in older populations from various clinical settings for criterion and predictive validation. Recent findings: Criterion validity studies, by comparing the GLIM construct with various semi-gold standards such as SGA, PG-SGA, MNA-FF/SF and ESPEN criteria, indicate by sensitivity, specificity and agreement that GLIM performs at least as well as the other tools to capture malnutrition. One meta-analysis of 20 studies with various comparators reports high accuracy for distinguishing malnutrition. GLIM-malnutrition prevalence figures vary with screening tool. Predictive validity of GLIM for mortality, and other outcomes, is good in all settings reported. Sarcopenia and GLIM show some expected overlapping. Summary: In populations more than 60 years old, the GLIM construct appears to have well acceptable criterion validity as well as predictive validity. The continuous implementation of the GLIM concept is justified.